Evaluation of aquatic contamination in an urban lagoon environment in a coastal region in the north of Brazil - Gomes, Janderson Bruzaca; Pereira, Natália Jovita; de SOUSA, Elielma Lima [UNESP]; Sousa, Denise da Silva; Lenz, Tiago de Moraes; Santos, Débora Martins Silva (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2019)
The quality of water is related to how it is used and how its physical, chemical and biological conditions are evaluated. The use of different evaluation tools can therefore provide accurate data about the environmental quality of aquatic ecosystems. The objective of the present study was to evaluate the aquatic contamination of the Laguna da Jansen Ecological Park in São Luís, in the state of Maranhão, Brazil, using different tools (physical variables, microbiological analysis and erythrocytic and gill alterations in Oreochromis niloticus). The microbiological analysis of the water was based on the identification of the most probable number (MPN) of total and thermotolerant coliforms using a chromogenic and fluorogenic enzymatic substrate test (MUG), while the physical-chemical parameters determined were temperature, pH, turbidity and dissolved oxygen. The fish were captured and then anaesthetized for the blood collect by gill puncture. Blood smear slides were prepared and stained with modified Rosenfeld staining for the evaluation of erythrocyte alterations. For histopathological analysis of the gills, the second left branchial arch was removed from each specimen and fixed in 10% formaldehyde for 24 hours. These were subsequently decalcified in 10% nitric acid and histological protocols in paraffin. Large numbers of erythrocyte alterations, notably micronuclei, were identified. Among the most common branchial alterations were lamellar epithelium lifting, blood capillary dilation, aneurysms, and total and partial lamella fusion. The result of the microbiological analysis of the water revealed a quantity of thermotolerant coliforms than is permitted under current legislation. These results indicate that the health of the animals has been damaged, pointing out the poor quality of the water in the Laguna da Jansen.
Avaliação da contaminação aquática em uma laguna costeira urbana no norte do Brasil
Keywords: Coliforms; Gills; Injuries; Micronucleus; Oreochromis niloticus